2008
DOI: 10.1021/pr800460y
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Analysis of Potato under Salt Stress

Abstract: Because salt stress is a major abiotic source of stress on potato crops, the molecular mechanism of the response of potato plants to salt stress was examined. On exposure to salt, the salt-sensitive cultivar Concord showed a greater reduction in shoot and root length than did the salt-tolerant cultivar Kennebec. For both cultivars, the reduction in the length of shoots was more severe than that of the roots. Salt exposure increased the content of free proline and total soluble sugars in shoots of Kennebec; the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
101
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(112 citation statements)
references
References 40 publications
11
101
0
Order By: Relevance
“…Our results are in general agreement with other studies showing that both photochemical and biochemical aspects of photosynthesis are affected by salinity (Hasegawa et al, 2000;Zhu, 2003;Dubey, 2005;Aghaei et al, 2008).…”
Section: Resultssupporting
confidence: 93%
“…Our results are in general agreement with other studies showing that both photochemical and biochemical aspects of photosynthesis are affected by salinity (Hasegawa et al, 2000;Zhu, 2003;Dubey, 2005;Aghaei et al, 2008).…”
Section: Resultssupporting
confidence: 93%
“…Of these, spots 7, 21, 22 and 40 had increased abundance levels, while spots 13 and 14 had reduced abundance levels following salt stress. The upregulation of protein expression observed here has also being documented in other studies on the proteomic analysis of potato shoots [21] and rice leaf lamina [20] under salt stress. The ATP synthase complex produces ATP from ADP in the presence of a proton gradient across the thylakoid membrane [56,57], which is in turn used for various energy demanding activities during periods of stress.…”
Section: Energysupporting
confidence: 86%
“…Rubisco which catalyses the carbon fixation reaction in photosynthetic plants [52] has an increased abundance in all four spots (spots 16-19; Table 1) in response to salt stress. In contrast, increased degradation of Rubisco was reported in the proteomic analysis of potato under salt stress [21], sugar beet under drought stress [53], rice under chilling stress [54], and maritime pine seedlings under water stress [55]. However, in another proteomic study involving sorghum leaf under salt stress, the expression of Rubisco was not shown to be altered in response to salt stress [23].…”
Section: Energymentioning
confidence: 99%
See 1 more Smart Citation
“…This indicated that ATP synthesis activity is enhanced, likely because plants need an increased energy production to deal with NH4 + toxicity. Similar observations have been reported in wheat (Wang et al, 2008b) and potato (Aghaei et al, 2008) under saline stress and Masson's pine under acid rain stress (Wang et al, 2013), indicating that sustained ATP synthesis is a common strategy for as plants under stress.…”
Section: Discussionsupporting
confidence: 82%